„Kolektywne” prawa człowieka źródłem ochrony mniejszości? - Lohmann, Georg; Byczyński, Marcin (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
Protection of minorities is a current and worldwide political problem. Therefore, the article discusses Will Kymlicka’s proposals regarding an idea of a ‘collective’ right, that is, a right of which a holder is a collective. This kind of a right is supposed to extend the canon of human rights in order to include the collective rights (as human rights of the third generation).